Examining the infographic design instructional process in terms of prospective mathematics teachers’ infographic design proficiency, self‑efficacy, and abilities in evaluating student errors: A model proposal - Neslihan Usta; Ali Özkaya; Gözdegül Arık Karamık; Yusuf Akın (PLoS ONE, 2026)
The rapid integration of digital visualization tools into teacher education programs has created new opportunities for enhancing instructional design skills in mathematics education. This study investigates the impact of a technology-enhanced infographic design instructional process on prospective mathematics teachers’ proficiency in digital infographic creation, their self-efficacy beliefs regarding technology-supported design and their abilities to evaluate middle school students’ errors in the data processing learning domain. The proposed cyclical model integrates these dimensions into the digital infographic design process, utilizing cloud-based design platforms (e.g., Canva, Piktochart) to foster technological pedagogical content knowledge. The research was conducted with 45 prospective mathematics teachers enrolled in an elementary mathematics teacher education program at a public university in Türkiye’s Mediterranean region during the 2021–2022 academic year. Data were collected through the Infographic Design Proficiency Rubric, the Infographic Design Self-Efficacy Scale, and pre- and post-tests on error evaluation. A single-group pre-test post-test quasi-experimental design was applied, supported by descriptive and content analyses of the digitally created infographics. Correlational analyses explored the relationships among the dependent variables. Findings revealed significant improvements in participants’ technology-supported infographic design proficiency, self-efficacy perceptions, and error evaluation abilities. These results highlight the potential of integrating digital visualization tools into mathematics teacher education, and the study recommends their broader adoption to enhance instructional quality and learner engagement in STEM education.